Role of Cooperative Governance Practices: A Study on Financial Cooperatives in Kerala: Bridging the Gap: Improving Cooperative Governance Practices in Financial Cooperatives (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This article focuses on Co-operative Governance practices of financial co-operatives in Kerala— including co-operative theory, demutualization, leadership, management, community, and social engagement (member or stakeholder voice), and policy. The study creates learning opportunities for students and leaders, by exploring how different factors work together to produce successful co-operative development. The study looks for the best, proven insights from around the world and for ways these can be adapted and applied in Kerala State. Considering the fact that financial co-operatives being financial institutions nearest to the people’s needs and wants are mandated to follow standard governance practices, there is a dire need to improve governance mechanism of these co-operatives. There are glimpses of good governance initiatives like standard governance practices of co-operatives (Co-operative Principles and values) issued by ICA that can be applied for better management of co-operatives. The evidences show that some Standard Governance Practices would be a better tool for ensuring effective management practices of financial co-operatives and thereby improving performance. Even though the Government directives stipulate standard in governance mechanisms of financial co-operatives, proper policy framework for tools like Standard Co-operative Governance Practices have not been developed so far. There is a gap in knowledge for the formulation of policy framework and management tools that best fit into the financial co-operatives. Encountering this problem, the present study looks into the issues raised.